Boron Doped Diamond/Metal Nanoparticle Catalysts Hybrid Electrode Array for the Detection of Pesticides in Tap Water. (2016) - Belghiti, D.K.; Zadeh-Habchi, M.; Scorsone, E.; Bergonzo, P.
Abstract: Online control of the chemical composition of drinking water is one of the major challenges of our century. This issue is addressed in this work with the development of a multi-electrode array based on Boron Doped Diamond (BDD) electrodes coated with metal catalyst nanoparticles. A new physical deposition method of the nanoparticles was developed, which offers good stability in terms of electro-activity and adhesion. The sensor array was tested for the electrochemical detection of pesticides including paraoxon and imidacloprid with good discrimination between both samples. For safety reason, hydrogen peroxide was also use as an efficient redox stimulus to assess the capability of the array to operate in tap water. The detection threshold was in the order of 19 ×10 -2 μM and 33×10 -2 μM for paraoxon and imidacloprid, respectively, as measured by chronoamperometry. Chronoamperometric method demonstrated also the potential of the array to operate online directly in tap water through the detection of H2 O2 .